Introducing a Dataset of Multi-Scale Geographies of ISIS Ideology from ISIS Sources - Fuhriman, Christopher (Terrorism and political violence, 2022)
This research proposes a methodology for extracting and analyzing geographical perspectives of terrorists and insurgents from online textual media. The information age has afforded organizations platforms that can be used to control their own media messages. Given that power, terrorist groups are able to create customized messages and define themselves in their own eyes on an international scale, often generating widespread sympathies and increased popularity. Within their online messaging, important information is provided that can potentially unveil geopolitical strategies. A mixed-method approach comprised of computer-aided content analysis, manual content analysis, and cartographic visualization is applied to ISIS’s Dabiq magazine as a case study to demonstrate the utility of this methodology. This research highlights the importance of considering the territoriality of terror groups and movements in geohistorical and present-day contexts.